2016
DOI: 10.1158/1078-0432.ccr-15-0548
|View full text |Cite|
|
Sign up to set email alerts
|

Well-Differentiated Neuroendocrine Tumors with a Morphologically Apparent High-Grade Component: A Pathway Distinct from Poorly Differentiated Neuroendocrine Carcinomas

Abstract: Purpose Most well-differentiated neuroendocrine tumors (WD-NETs) of the enteropancreatic system are low-intermediate grade (G1,G2). Elevated proliferation demonstrated by either a brisk mitotic rate (>20/10 high power fields) or high Ki67 index (>20%) defines a group of aggressive neoplasms designated as high grade (G3) neuroendocrine carcinoma (NEC). High grade NEC is equated with poorly-differentiated NEC (PD-NEC) and is associated with a dismal outcome. Progression of WD-NETs to a high grade neuroendocrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
260
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(284 citation statements)
references
References 26 publications
(37 reference statements)
14
260
2
3
Order By: Relevance
“…However, only in 5% (3/60) of cases this resulted in change of grade from G1 to G2 [15]. This value could be underestimated, since higher grade component may form a minor portion of the tumour [9]. Valous et al showed that lacunarity measurement allows categorization of samples of pancreatic NEN to groups with homogenous or with heterogenous spatial Ki-67 LI distribution across whole virtual sections [10].…”
Section: Ki67 LI Heterogeneity Beyond Single Hs or Csmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only in 5% (3/60) of cases this resulted in change of grade from G1 to G2 [15]. This value could be underestimated, since higher grade component may form a minor portion of the tumour [9]. Valous et al showed that lacunarity measurement allows categorization of samples of pancreatic NEN to groups with homogenous or with heterogenous spatial Ki-67 LI distribution across whole virtual sections [10].…”
Section: Ki67 LI Heterogeneity Beyond Single Hs or Csmentioning
confidence: 99%
“…Ki67 LI heterogeneity was observed not only within primary tumour tissue [9,10,11,12], but also between primary and metastatic lesions [13,14,15] and within and between metastases [16,17].…”
Section: Introductionmentioning
confidence: 97%
“…SSTR positivity is an important finding for demonstrating that a lesion is in fact a NET; therefore, to characterize a finding on CI, SSTR PET can be used to clarify whether a suspected lesion is a NET and represents true progression or recurrence. In addition, it is possible for NETs to dedifferentiate, changing from welldifferentiated to poorly differentiated NETs over time (49). SSTR PET can be an indirect indicator of grade, and therefore reimaging at the time of progression can provide insight into possible underlying dedifferentiation of a tumor.…”
Section: Scenario 6: Monitoring Of Nets Seen Predominantly On Sstr Pementioning
confidence: 99%
“…These cases (G3 well-differentiated GEP-NETs) generally have histologic features in common with other well-differentiated NETs, and in most cases, only the Ki67 index-not the mitotic rate-falls in the G3 range. Available genetic information also suggests that G3 well-differentiated GEPNETs share molecular alterations with their lower grade GEP-NET counterparts, and they lack the mutations commonly found in poorly differentiated neuroendocrine carcinomas (e.g., TP53 and RB1 ) [12]. Although G3 welldifferentiated GEP-NETs are more aggressive than G1 and G2 GEP-NETs, they are not as aggressive as true poorly differentiated neuroendocrine carcinomas.…”
mentioning
confidence: 99%
“…Progression of a G1 or G2 GEP-NET to a higher grade (even G3) can occur with metastatic progression [12]. Therefore, reassessment of the grade of a previous specimen such as the primary tumor may not reflect the biology of the active disease.…”
mentioning
confidence: 99%